Pengembangan Media Gamifikasi Berbantuan Crossword Puzzle untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Informatika Kelas VIII SMP - Salsa Elza Monika; Zelhendri Zen; Meldi Ade Kurnia Yusri; Khairul Alfahani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to develop a web-based HTML5 gamification learning media in the form of a digital crossword puzzle on the topic of Digital Literacy that meets valid, practical, and effective qualifications. This study was a Research and Development (R&D) project using the 4D development model (Define, Design, Develop, and Disseminate). Data collection instruments included expert validation sheets (material and media), practicality questionnaires (student responses), and effectiveness scales (user engagement questionnaires). Data were analyzed using both quantitative and qualitative methods. The results showed that: (1) The material validity test by educational practitioners achieved a score of 92% (